5.25.4 Problems 301 to 400

Table 5.1105: Second order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

6390

\[ {}x^{\prime \prime }+42 x^{\prime }+x = 0 \]

6504

\[ {}\frac {x^{\prime \prime }}{2} = -48 x \]

6546

\[ {}y^{\prime \prime }-y = 0 \]

6551

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

6557

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 0 \]

6573

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

6575

\[ {}y^{\prime \prime }-y = 0 \]

6577

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

6691

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

6701

\[ {}y^{\prime \prime }+2 y^{\prime }-15 y = 0 \]

6703

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

6705

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

6706

\[ {}y^{\prime \prime }+25 y = 0 \]

6888

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 0 \]

6898

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

6908

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

6909

\[ {}2 y^{\prime \prime }+7 y^{\prime }-4 y = 0 \]

6939

\[ {}x^{\prime \prime }+x = 0 \]

6940

\[ {}x^{\prime \prime }+x = 0 \]

6941

\[ {}x^{\prime \prime }+x = 0 \]

6942

\[ {}x^{\prime \prime }+x = 0 \]

6943

\[ {}y^{\prime \prime }-y = 0 \]

6944

\[ {}y^{\prime \prime }-y = 0 \]

6945

\[ {}y^{\prime \prime }-y = 0 \]

6946

\[ {}y^{\prime \prime }-y = 0 \]

6971

\[ {}y^{\prime \prime }+4 y = 0 \]

6972

\[ {}y^{\prime \prime }+4 y = 0 \]

6973

\[ {}y^{\prime \prime }+4 y = 0 \]

6974

\[ {}y^{\prime \prime }+4 y = 0 \]

6975

\[ {}y^{\prime \prime }+4 y = 0 \]

6976

\[ {}y^{\prime \prime }+4 y = 0 \]

6988

\[ {}y^{\prime \prime } = y^{\prime } \]

7349

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

7351

\[ {}y^{\prime \prime }-\frac {y}{4} = 0 \]

7354

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

7358

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

7362

\[ {}9 y^{\prime \prime }-6 y^{\prime }+y = 0 \]

7478

\[ {}y^{\prime \prime }+2 y^{\prime }-y = 0 \]

7517

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

7518

\[ {}s^{\prime \prime }+2 s^{\prime }+s = 0 \]

7519

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

7585

\[ {}y^{\prime \prime }-y = 0 \]

7586

\[ {}y^{\prime \prime }+4 y = 0 \]

7587

\[ {}y^{\prime \prime }+k^{2} y = 0 \]

7612

\[ {}y^{\prime \prime }-4 y = 0 \]

7613

\[ {}3 y^{\prime \prime }+2 y = 0 \]

7614

\[ {}y^{\prime \prime }+16 y = 0 \]

7615

\[ {}y^{\prime \prime } = 0 \]

7616

\[ {}y^{\prime \prime }+2 i y^{\prime }+y = 0 \]

7617

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 0 \]

7618

\[ {}y^{\prime \prime }+\left (-1+3 i\right ) y^{\prime }-3 i y = 0 \]

7619

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

7620

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

7621

\[ {}y^{\prime \prime }+y = 0 \]

7622

\[ {}y^{\prime \prime }+y = 0 \]

7623

\[ {}y^{\prime \prime }+y = 0 \]

7624

\[ {}y^{\prime \prime }+y = 0 \]

7625

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 0 \]

7626

\[ {}y^{\prime \prime }+\left (1+4 i\right ) y^{\prime }+y = 0 \]

7627

\[ {}y^{\prime \prime }+\left (-1+3 i\right ) y^{\prime }-3 i y = 0 \]

7628

\[ {}y^{\prime \prime }+10 y = 0 \]

7650

\[ {}y^{\prime \prime }+y = 0 \]

7651

\[ {}y^{\prime \prime }-y = 0 \]

7657

\[ {}y^{\prime \prime }-2 i y^{\prime }-y = 0 \]

7762

\[ {}y^{\prime \prime }+k^{2} y = 0 \]

7777

\[ {}y^{\prime \prime }+4 y = 0 \]

7778

\[ {}y^{\prime \prime }-4 y = 0 \]

7804

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 0 \]

7907

\[ {}y^{\prime \prime }-k^{2} y = 0 \]

7937

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

7938

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

7939

\[ {}y^{\prime \prime }+8 y = 0 \]

7940

\[ {}2 y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

7941

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

7942

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 0 \]

7943

\[ {}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

7944

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

7945

\[ {}y^{\prime \prime }+y = 0 \]

7946

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

7947

\[ {}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0 \]

7948

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

7949

\[ {}y^{\prime \prime } = 4 y \]

7950

\[ {}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0 \]

7951

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

7952

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7953

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7954

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

7955

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

7956

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

7957

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

7958

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7959

\[ {}y^{\prime \prime }+4 y^{\prime }+2 y = 0 \]

7960

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

8005

\[ {}y^{\prime \prime }+y = 0 \]

8006

\[ {}y^{\prime \prime }-y = 0 \]

8039

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

8040

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8041

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

8042

\[ {}y^{\prime \prime }-y^{\prime }+6 y = 0 \]

8047

\[ {}y^{\prime \prime }+9 y = 0 \]